Comparison of radiographic arthritic changes associated with two variations of tibial plateau leveling osteotomy - Lineberger, J. A.; Allen, D. A.; Wilson, E. R.; Tobias, T. A.; Shaiken, L. G.; Shiroma, J. T.; Biller, D. S.; Lehenbauer, T. W. (Veterinary and Comparative Orthopaedics and Traumatology, 2005)
Osteoarthritis (OA) progresses in the canine cranial cruciate ligament (CCL) deficient stifle. Progression of OA is also documented in canine patients after various surgical repair techniques for this injury. We evaluated the radiographic arthritic changes in canine stifle joints that have sustained a CCL injury, and compared radiographic OA scores between Tibial Plateau Leveling Osteotomy (TPLO.)surgery patients receiving a medial parapatellar exploratory arthrotomy for CCL remnant removal versus those receiving a limited caudal medial arthrotomy without removal of the CCL remnants. Medial/ lateral and caudal/cranial stifle radiographs were obtained before surgery, immediately following TPLO surgery and at 7–38 months (mean 20.5) after surgery. Sixty-eight patients (72 stifles) were included in the study. The cases were divided into two groups. The patients in group 1 (n = 49 patients, 51 stifles) had a limited caudal medial arthrotomy, and patients in group 2 (n = 19 patients, 21 stifles) had a medial parapatellar open arthrotomy. A previously described radiographic osteoarthritis scoring system was used to quantify changes in both of the groups. The age, weight, OA scores, initial tibial plateau angle, final tibial plateau angle, and the change in angle were compared between the groups. The results showed that there was significantly less progression of OA in the group that had the limited caudal medial, arthrotomy, versus a medial parapatellar open arthrotomy. There was a significant advancement of the OA scores of patients that had TPLO surgery.
Keywords: Cranial cruciate disease; osteoarthritis; TPLO®; radiographic assessment; canine